Molecular identification of Moniliophthora roreri isolates from cocoa orchards in Norte de Santander, Colombia - Liliana Yanet Suárez Contreras (Acta Agronómica)
The plant pathogenics fungus Moniliophthora roreri, causes losses to cocoa farmers and it causes the “Moniliasis”, too. The disease destroys the cocoa pod and crop production decreases, the losses reach up to 60% in the department of Norte de Santander. Little is known of the biology of the fungus, studies are currently identifying macroscopic, microscopic, and behavior in vitro with antagonists such as Trichoderma asperellum, Trichoderma longibrachiatum, Paecilomyces sp. and Bacillus brevis. Fifty-six isolates of M. roreri were obtained from 8 municipalities and townships the department (El Zulia, Cucuta, Tibú, Sardinata, Bucarasica, Teorama, Agua clara, El Tarra) for the purpose of DNA extraction and PCR analysis. The method of isolation was performed from infected ears M. roreri, which were washed with distilled water, and cut into 2 x 2 cm, and were disinfected with hypochlorite, 2.5% sodium and 60% alcohol. Then sown in Petri dishes containing PDA medium and incubated for 10 days at 28 ° C. Ribosomal regions “ITS” (internal transcribed spacers) for the 18S rDNA, ITS1, 5.8S, ITS2 and 25S, were amplified and sequenced. Amplicons of 600 bp (8 isolates), 740 bp (12 isolates) and 750 bp for the remaining 36 isolates. The sizes of the amplicons corresponded to those expected for the species M. roreri, and analysis “BLAST” level confirmed this characterization.